The Currency of Water in Words: An Analysis of the Conceptual Metaphors of Water - PERSAUD, SONIA (My University, 2022)
This dissertation is a study of water metaphors in the theoretical framework of feminist environmental humanities. It draws on feminist theory, metaphor theory, and Indigenous theories. It examines some of the water metaphors enshrined in Canadian legislation, specifically the Fisheries and Oceans Act and the Canada Water Act. It also examines some of the water metaphors in Canadian literature, focusing on creative works by Lisa Moore, Rita Wong, and Leanne Betasamosake Simpson. I argue that a dialogue between metaphor theory and feminist theory radically transforms the scope for understanding water in a way that not only consolidates the presence of materiality, but initiates a trajectory into the discursive and creative modes of metaphor that enable the interrogation of the politics of water. As a settler Canadian, I position this dialogue in relation to Richard W. Hill Sr. and Daniel Coleman’s metaphor of the Two Row Wampum-Covenant Chain Treaty to frame the conversation between the Indigenous and settler Canadian texts that I examine in this dissertation. Following a reparative arc, I analyze the metaphors of water to reveal the discrepancy between some of the legislative and creative metaphors. I conclude that the analytical lens of metaphor contribute to a greater understanding of how the conceptual metaphors of water we employ reflect our embodied experience of water and how historically marginalized as well as new metaphors can shape our values and ideas about water in the Anthropocene. I also conclude that the theoretical intersection of water and metaphor constitutes a powerful foundation from which to reimagine metaphor’s shared materiality and efficacy with water. This study affirms the value of a cultural intervention in the praxis of the water issues of the Anthropocene.
Keywords: Water, Metaphor, Environmental Humanities, Cultural Studies, Canadian Literature